The Effect of some Variables on the Formulation of Captopril as Tablets Shaymaa Nazar Al â€" Sammarrai - Dr. Alaa A. Abdul R asool; Dr. Hikmet Al â€" Dujali (College of Pharmacy University of Baghdad, 2017)
Captopril is an angiotensin converting enzyme inhibitor (ACEI) used to treat hypertension, congestive heart failure, and myocardial infraction. The only dosage form available for captopril is the plain tablet in strength of 12.5,25,50 and 100mg tablet. This investigation is concerned with factors affecting the formulation of captopril as a plain tablet dosage form of 50mg. Many trials were made to prepare satisfactory tablets for the drug by using wet â€" granulation methods with various additives. It was found that poly vinyl pyrrolidone (P.V.P.) as binder gave the most satisfactory tablets. At the same time a shorter disintegrantion time and slower dissolution rate were obtained with the addition of starch intragranular. While the distintegration time and dissolution rate were faster for explotab when it was used intragranular in comparison with starch. A comparative study on the physical properties of the prepared tablets with CapotenÂ® (Squibb), MinitenÂ® (APM), and CapocardÂ® (DAD) tablets, showed that the release of drug from the selected formula was similar to that obtained from MinitenÂ® at 0.1N HCl and 37C. The stability of the prepared tablet was also studied at 50ï,°C, 60ï,°C, and 70ï,°C for 4 months and the calculated shelf â€" life was about 3.5years at 25C.